Cultivation to consumption: strengthening bacterial safety in plant-based nutraceuticals - Gaur, Ashish; Singhal, Nishant; Vardhan, Harsh; Jain, Rajul; Bist, Yograj; Wagri, Naresh Kumar (Frontiers in Microbiology, 2025)
Plant-based nutraceuticals are increasingly recognized for their bioactive compounds that promote health and assist in preventing chronic diseases. However, the rising demand has raised concerns about microbial safety, as contamination can occur at multiple stages of the production process-ranging from cultivation and harvesting to processing, storage, and distribution. Pathogens such as Escherichia coli, Salmonella, Listeria monocytogenes, and toxin-producing fungi pose risks to product quality, threaten consumer health, and contribute to antimicrobial resistance. This review provides a comprehensive overview of the sources and types of microbial contamination, associated health risks, and the shortcomings of conventional control methods. It highlights recent advancements in safety techniques, including cold plasma, ultraviolet light treatment, high hydrostatic pressure, nanocoatings, probiotic biocontrol, and AI-driven microbial monitoring. Additionally, the analysis addresses the role of regulatory frameworks, quality assurance practices, and consumer education as integral elements of a unified safety approach. It integrates technological progress, regulatory perspectives, and consumer behavior to offer a detailed guide for ensuring the microbial safety of plant-derived nutraceuticals, thereby fostering confidence in these products from production through to consumption.